Pelatihan WhatsApp Telemedicine Stunting untuk Meningkatkan Literasi Kader Posyandu di Desa Lokus Stunting Kabupaten Banyumas - Pantiawati, Ika; Wulan, Widya Ratna; Widianawati, Evina; Fani, Tiara; Kusuma, Edi Jaya; Ananda, Nurrisa (Jurnal Pengabdian UNDIKMA, 2024)
The community service aims to increase the literacy and skills of Posyandu cadres in preventing stunting of toddlers as an effort to support the success of the 2030 SDGs in Banyumas Regency. The method of implementing this service used assistance and practice carried out on mothers who had stunted toddlers in Lokus Stunting Village, Banyumas Regency. Detailed activities included preparation, pre-test, providing education, training on the WhatsApp Telemedicine Stunting application and post-test. The evaluation instrument for this activity used a questionnaire and was explained descriptively. The results of this service showed that above average participants experienced an increase in Stunting Telemedicine Knowledge before and after the training by 87%, indicating that participants’ Stunting Telemedicine Knowledge increased compared to before the training. The Toddler Stunting Knowledge aspect before and after mentoring also experienced an increase of 4%, then there was the Toddler Nutrition Knowledge aspect with an increase of 7%. The implications that can be taken from this service were increasing the literacy of Posyandu cadres, improving knowledge of toddlers with stunting, increasing knowledge of toddler nutrition, as well as contributing to SDGs 2030.